Impact of land use conservation of swampy lowland urban areas on people's awareness and perception - Yusuf, Maulana; Damiri, Nurhayati; Saptawan, Ardiyan; Aslamiah, Nur; Usman, Fathoni; Affandi, Ahmad; Rahim, Supli E; Yunardy, Syafrul (Journal of Degraded and Mining Lands Management, 2025)
This study investigated how changes in land use impact people's knowledge and perceptions, notably the transformation of wetlands into residential and industrial sectors in urban low-lying areas. This transformation's accelerating urbanization is a worldwide phenomenon fueled by infrastructural growth and urban growth. This study was carried out using a mixed-methods approach that includes surveys, interviews, and spatial analysis. This research showed a complicated link between a change in land use and how people perceive it. First, turning low-lying swamps into cities frequently changes the hydrological dynamics, raising the risk of floods and other water-related risks. As a result, people who live in transformed areas tend to develop more conscious of these environmental dangers. However, this increased awareness may not always result in proactive mitigating actions due to resource shortages and poor urban planning. Second, socio-economic position and proximity to redeveloped regions affect how locals view urban growth. While some regard land use conversion adversely owing to habitat loss and potential health hazards related to pollution and sanitation difficulties, others see it as a chance for economic expansion and improved infrastructure. Lastly, minimizing the negative effects of land use shifts depends on efficient urban planning and community involvement. People's perceptions are more likely to be positive when they participate in decision-making processes and access information and resources, increasing engagement in sustainable urban development activities.